Design and development of an anthropomorphic shoe-tying robot - Ramli, Mohd Syamsul; Zainul Azlan, Norsinnira (2014)
In the last decades, there have been an increasing interest among the researchers to develop robots or robot parts that have close functionally and appearance as human. This paper presents the development of a pair of anthropomorphic robotic hand to perform shoe-tying task to assist the elderly and handicapped, and also for prosthetics and humanoid robot applications. The robotic hand has a close appearance as human hand, consisting of the shoulder, wrist and five fingers. The real human hand operation while tying shoes has been observed in designing the mechanism and operational step. The forward and inverse kinematics of the robotic hand has been analyzed and the inverse kinematics analysis is used to determine the corresponding angular displacement of the joints with respect to the desired position in Cartesian axis. A prototype equipped with Arduino Mega 2560, gyro meter, Force Sensitive Resister (FSR) and servomotors has been built. The success rate of the robot is 100% under manual mode and 60% under automatic mode.